Action Meets Word 2006
DOI: 10.1093/acprof:oso/9780195170009.003.0018
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Noun-Verb Debate: A Cross-Linguistic Comparison of Novel Noun and Verb Learning in English-, Japanese-, and Chinese-Speaking Children

Abstract: To understand the nature of lexical development, it is crucial to investigate how children learn a wide range of word classes, including nouns, verbs, and adjectives, along with closed class words such as prepositions and classifiers. An important question is whether a particular type of concept, over others, universally invites children to name it at early stages of word learning to serve as the entry point into language, that is, whether there is, in Gentner's words, "an initial set of fixed hooks with which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
(47 reference statements)
1
22
0
Order By: Relevance
“…Because of the advanced age of these participants, pointing replaced visual fixation as the dependent measure. This substitution has been made in prior research with 3-year-olds, generating results comparable to looking time data (Imai et al, 2006;Maguire, Pruden, Hirsh-Pasek, Hansel, & Meyer, 2004). Prior to beginning the video, the experimenter explained to children that they would be playing a pointing game.…”
Section: Methodsmentioning
confidence: 79%
See 2 more Smart Citations
“…Because of the advanced age of these participants, pointing replaced visual fixation as the dependent measure. This substitution has been made in prior research with 3-year-olds, generating results comparable to looking time data (Imai et al, 2006;Maguire, Pruden, Hirsh-Pasek, Hansel, & Meyer, 2004). Prior to beginning the video, the experimenter explained to children that they would be playing a pointing game.…”
Section: Methodsmentioning
confidence: 79%
“…Research is accumulating to suggest that linguistic information can alter preliminary perceptual preferences (e.g., Behrend, Harris, & Cartwright, 1995;Echols & Marti, 2004;Fisher, 2002;Imai et al, 2006;Maguire, 2004;Naigles & Kako, 1993). For example, Naigles and Kako (1993) demonstrated that before the age of 30 months, children can use syntactic information, particularly that encoded in the transitive verb frame, to redirect or refocus their attention on a less favored action (e.g., a causative action), thereby leading to a successful mapping.…”
Section: Solution 2: Attention To Linguistic and Social Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, further evidence was provided for the significance of the noun, and its universal predominance has been shown in a multitude of studies (e.g., Gentner, 2006;Imai, Haryu, Okada, Li, & Shigematsu, 2006). Generally, researchers have focused on nouns and verbs, but barely or not at all on adjectives and closed-class words (Dürr & Schoblinski, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is also not the case that the noun advantage occurs only in 'noun-friendly' languages that possess linguistic properties (e.g., word order, word frequency, stress patterns) that might make nouns more salient than other forms (Gentner, 1982). A noun advantage in early vocabularies has been reported in 'verb-friendly' languages as well, including Korean (Au, Dapretto, & Song, 1994), Japanese (Ogura, 2001, as cited in Imai et al, 2006), Italian (Caselli et al, 1995), and Navajo (Gentner & Boroditsky, 2001). Although there is some debate concerning the cross-linguistic evidence for the noun advantage (e.g., Choi & Gopnik, 1995;Tardif, Gelman, & Xu, 1999), the controversy appears to reflect methodological issues: Research based on parental reports of their infants' vocabularies consistently reports a noun advantage, while research based on infants' spontaneous language production in interactive play sessions sometimes does not (Lavin, Hall, & Waxman, 2006).…”
mentioning
confidence: 95%